2-Local superderivations on the super Virasoro algebra and the super W(2, 2) algebra. Issue 12 (2nd December 2021) - Dilxat, Munayim; Gao, Shoulan; Liu, Dong
Abstract: The present paper is devoted to studying 2-local superderivations on the super Virasoro algebra and the super W ( 2, 2 ) algebra. It is proved that all 2-local superderivations on the super Virasoro algebra as well as the super W ( 2, 2 ) algebra are (global) superderivations.